Knowledge and utilization of health informatics among medical doctors in Ahmadu Bello University Teaching Hospital, Shika-Zaria - Jamila Mohammed Dahiru (International Journal of Informatics and Communication Technology (IJ-ICT), 2021)
The strategic visions in the health care system now underpin application of Information Communication Technology for effective care delivery. Recognising the potentials of ICT for Health, the Nigerian government as part of its policy derive towards achieving effective health care delivery by the year 2020, adopted use of ICT for effective healthcare delivery. Part of the target was establishment of ICT/Health informatics units in teaching hospitals in the country. This study assessed level of knowledge and utilization of health informatics among medical doctors in Ahmadu Bello University, Shika-Zaria. Premised on the Unified Theory of Acceptance and Use of Technology, this study adopted descriptive survey method and structured questionnaire as its instrument of data collection. Findings revealed that 91.4% (n=201) of the 220 sampled medical doctors in ABUTH are aware of health informatics and that 68.2% (n=150) have knowledge of how to use it. The most prominent areas of health informatics among the medical doctors are ‘Management Information System’, ‘Electronic Health Record System’ and ‘Electronic Medical Record’. However, only 58.6% (n=129) of the medical doctors in BUTH Shika- Zaria are actually utilizing health informatics. Internet (n=133, 60.5%) and interpersonal sources (n= 71, 32.3%) were found to be the major sources of information of knowledge and utilization of health informatics among the medical doctors. The study therefore recommends that ABUTH, Shika-Zaria should put in place more mechanism for creating awareness on use of health informatics varieties and a strong need for time-series research to examine future development in respect to knowledge and utilization of health informatics in Nigerian health institutions.